Quantitative Impact of Current Harmonics on Electromagnetic Lossesi n Automotive PMSMs - Rener, Krištof; Treven, Martin; Kovačič, Robert; Kovačič, Uroš; Černe, Tomaž; Mousavi, Mohammad; Naderi, Roozbeh (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper investigates the quantitative impact of current harmonics on electromagnetic losses in PMSMs used in automotive applications. We compare losses generated by sine current with those produced by conventional 2-level SVPWM inverter. A dynamic model is developed to capture the interaction between the 2-level inverter and the PMSM, accurately predicting the resulting harmonic currents. These predicted currents are then used as input for a FEA to calculate the electromagnetic losses in various motor components. Our analysis reveals that current harmonics can significantly increase the total electromagnetic losses in the motor through the whole operating range.